Pengaruh Model Project Based Learning Terhadap Keterampilan Menulis Teks Narasi Siswa Sekolah Dasar - Asmila Damayanti; Akhiril Pane (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to examine the effect of implementing Project Based Learning (PjBL) on elementary school students’ narrative writing skills through a literature review. The analysis was conducted on five main articles discussing the implementation of PjBL, the use of interactive media, and its impact on students’ creativity, critical thinking, collaboration, and learning motivation. The findings indicate that PjBL effectively improves students’ abilities in structuring the orientation, complication, resolution, and coda of a story coherently, enriching vocabulary, and composing well-organized sentences. PjBL positions students at the center of learning, encouraging active participation, reflection, and collaboration, making the writing experience more meaningful and enjoyable. This review confirms that PjBL can serve as an effective strategy to enhance narrative writing literacy in elementary schools while addressing the research gap regarding the application of this model at the primary education level.